2020
DOI: 10.1101/2020.08.31.20169946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of SARS-CoV-2 receptor gene expression in upper and lower airways

Abstract: The recent outbreak of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), has led to a worldwide pandemic. One week after initial symptoms develop, a subset of patients progresses to severe disease, with high mortality and limited treatment options. To design novel interventions aimed at preventing spread of the virus and reducing progression to severe disease, detailed knowledge of the cell types and regulating factors driving cellular entry is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 38 publications
10
23
0
Order By: Relevance
“…TMPRSS2 expression is highest in AT2 cells, and is lower in the COPD samples ( Supplementary Fig. 4b), similar to a recent publication demonstrating decreased TMPRSS2 expression in severe COPD 42 . Two alternative priming proteases (CTSL and FURIN) showed no significant differences in expression between control and disease samples ( Supplementary Fig.…”
Section: Expression Profile Of Sars-cov-2 Associated Receptors and Fasupporting
confidence: 89%
See 1 more Smart Citation
“…TMPRSS2 expression is highest in AT2 cells, and is lower in the COPD samples ( Supplementary Fig. 4b), similar to a recent publication demonstrating decreased TMPRSS2 expression in severe COPD 42 . Two alternative priming proteases (CTSL and FURIN) showed no significant differences in expression between control and disease samples ( Supplementary Fig.…”
Section: Expression Profile Of Sars-cov-2 Associated Receptors and Fasupporting
confidence: 89%
“…Leung et al performed bulk RNAseq and immunohistochemical staining on bronchial epithelial cells and showed significantly elevated expression levels of ACE2 and ACE2 protein in the small airways of COPD patients compared to control 70 . Another study on bronchoscopically isolated tissue showed no relationship between disease status (mild to moderate asthma or COPD) on the expression levels of all SARS-CoV-2 entry factors 42 . Our study utilized scRNAseq technology to study gene expression at a very granular level and did not identify increased ACE2 expression at the single cell level in CLD, including COPD.…”
Section: Discussionmentioning
confidence: 95%
“…TMPRSS2 expression is highest in AT2 cells, and is lower in the COPD samples ( Supplementary Fig. 4b), similar to a recent publication demonstrating decreased TMPRSS2 expression in severe COPD 42 . Two alternative priming proteases (CTSL and FURIN) showed no signi cant differences in expression between control and disease samples ( Supplementary Fig.…”
Section: Expression Pro Le Of Sars-cov-2 Associated Receptors and Facsupporting
confidence: 89%
“…Leung et al performed bulk RNAseq and immunohistochemical staining on bronchial epithelial cells and showed signi cantly elevated expression levels of ACE2 and ACE2 protein in the small airways of COPD patients compared to control 70 . Another study on bronchoscopically isolated tissue showed no relationship between disease status (mild to moderate asthma or COPD) on the expression levels of all SARS-CoV-2 entry factors 42 . Our study utilized scRNAseq technology to study gene expression at a very granular level and did not identify increased ACE2 expression at the single cell level in CLD, including COPD.…”
Section: Discussionmentioning
confidence: 95%
“…proliferation in epithelial cells through co-expression of ACE2 [24]. Smoking status was found to increase the majority of COVID-19 related genes in the lower airways, which was associated with a significant increase in the predicted proportion of goblet cells in bronchial samples of smokers [25]. Smoking-mediated upregulation of the androgen pathway also leads to an increased SARS-CoV-2 susceptibility [26].…”
Section: Resultsmentioning
confidence: 92%